Waste to Wattage: Revolutionizing Camping with Sustainable Energy - Kamarul Ariffin, Khairina Ameera; Muhammad Aiman Kamal; Nurul Darwisyah Zakirah Noor-Al-Anuar; Mardiha Mokhtar (Multidisciplinary Applied Research and Innovation, 2025)
This project sets out on a multifaceted journey to deal with the growing problem caused by the increasing volume of non-biodegradable garbage. In this paper, a proposal and result were made to create a wattage from the non-biodegradable waste by converting the waste to energy using burning process. This project aims to examine and assess sustainable energy alternatives from waste material for camping in response to the limitations and environmental challenges posed by conventional camping energy sources, to develop a portable waste-to-energy system for camping with a focus on achieving notable improvements in energy efficiency sources and to assess the capability of converting material to energy by using multimeter test. This prototype requires coal that is obtained from non-biodegradable trash as the main resource. Next, the goal of a diligently planned process that includes in-depth research, continuous prototype development, and extensive trial and error to create a solution that not only reduces the negative effects of non-biodegradable waste but also exhibits resilience and adaptability in a variety of camping situations.